3D FINITE ELEMENT MODEL FOR THERMO-POROMECHANICAL DEFORMATION IN SEDIMENTARY BASINS - Brüch, André R. (2017)
Sedimentary basins form when an appreciable amount of sediments are deposited along geological time and transformed into rock through natural phenomena known as diagenesis. Compaction of sediments, fluid and thermal flows are fundamental coupled processes in sedimentary basin modelling. Purely mechanical phenomena prevail in the upper layers involving pore fluid expulsion and rearrangement of solid particles, while chemomechanical compaction resulting from Intergranular Pressure-Solution (IPS) dominates for deeper burial as stress and temperature increase. The thermal evolution of the basin may substantially affect both processes as heat modifies fluid viscosity and physicochemical properties of minerals, thus affecting fluid flow and mineral stability. The aim of the present contribution is to provide a comprehensive 3D framework for constitutive and numerical modelling of thermo-poro-mechanical deformation during diagenesis. Purely mechanical and chemo-mechanical deformations are respectively modelled by means of poroplastic and poroviscoplastic models. The numerical simulations are performed through the finite element method with a shared memory multiprocessing interface. The sedimentary basin is modelled as a fully saturated thermo-poro-elasto-visco-plastic material undergoing large strains. Special attention is given to temperature effects on the deformation history of the basin.